The Effect of Military Spending on Economic Growth and Unemployment in Mediterranean Countries - Korkmaz, Suna (International Journal of Economics and Financial Issues, 2015)
One of the necessities of public life and one of the basic elements of the state aiming to fulfill the demands and requirements of individuals which form the community is sovereignty. Sovereignty is separated into two as internal and external. This means, state should provide internal security and peace and also should be able to protect itself against the external threats. In order for a state to achieve these, it has to fulfill the defense services. Due to the unease in Arab regions after Arab spring and as Mediterranean region has strategic importance, 10 countries in Mediterranean region were selected and analysis with panel data was performed for years 2005-2012, in order to examine the effect of military spending of these countries on economic growth and unemployment. Keywords: military spending; economic growth; unemployment; panel data analysis. JEL Classifications: C51; E24; F5; H5; O11